2002
DOI: 10.1071/ah020071
|View full text |Cite
|
Sign up to set email alerts
|

The Victorian Ambulatory Care Sensitive Conditions Study: reducing demand on hospital services in Victoria

Abstract: Ambulatory Care Sensitive Conditions (ACSCs) are those for which hospitalisation is thought to be avoidable if preventive care and early disease management are applied, usually in the ambulatory setting. The Victorian ACSCs study offers a new set of indicators describing differentials and inequalities in access to the primary healthcare system in Victoria. The study used the Victorian Admitted Episodes Dataset (1999-2000) for analysing hospital admissions for diabetes complications, asthma, vaccine preventable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…20 In these data it was not possible to identify admissions that were specifically related to diabetes, but diabetes is a major contributor to hospitalisation. 21 A fifth of participants reported hospitalisation within the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…20 In these data it was not possible to identify admissions that were specifically related to diabetes, but diabetes is a major contributor to hospitalisation. 21 A fifth of participants reported hospitalisation within the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, evaluation of a limited sample of ACSCs found that higher community affluence and not living in a rural setting were associated with lower rates of admission for ACSCs [11]. An Australian study found a 12-fold variation in admission rates for diabetes complications and similar variation in admission rates for asthma, influenza and pneumococcal pneumonia [12]; there, lower income, educational achievement, and self-rated health status were associated with higher rates of admission for ACSCs [13]. An evaluation of admission for several chronic ACSCs in four large Italian cities showed that poorer people, females, and older people in the sample were more likely to be admitted for ACSCs [14].…”
Section: Introductionmentioning
confidence: 93%
“…The concept has also been adopted and modified by countries outside the USA, including Australia [15][16][17][18].…”
Section: Key International Researchmentioning
confidence: 99%
“…Incidence rates varied depending on the study population, with 2.4-3.6% of all hospital admissions being drug related, [15][16][17][18][19][20][21][22] …”
Section: Adverse Eventsmentioning
confidence: 99%